Early and middle Holocene ecosystem changes at the Western Carpathian/Pannonian border driven by climate and Neolithic impact. (23rd February 2018) - Šolcová, Anna; Petr, Libor; Hájková, Petra; Petřík, Jan; Tóth, Peter; Rohovec, Jan; BáTORA, JOZEF; Horsák, Michal
Abstract : Travertine deposits are unique archives for multidisciplinary studies of past climate changes, associated vegetation development and the evolution of human societies. Despite their high potential in palaeoecological and palaeoclimate reconstructions, investigations of travertines are rather scarce in central Europe and particularly in Slovakia. Therefore, this study focused on a travertine deposit situated on the border between the Pannonian Basin and the Western Carpathians in a small valley in Santovka village (SW Slovakia), which is unique due to the presence of archaeological artefacts with known radiocarbon ages in the palaeoecological profile. Using a multidisciplinary approach combining macrofossil, pollen, mollusc, lithological and geochemical analyses, this study investigated climate–human–vegetation interactions. The Holocene onset was marked by the early arrival of oak trees; however, forest‐steppe with a high representation of pine predominated until 9880 cal. a BP, followed by an expansion of temperate trees. The local ecosystem changed around 8600 cal. a BP when the valley was probably dammed by a travertine accumulation, probably resulting in the existence of a small travertine lake. This was associated with wetter climatic conditions, which were also documented in other sites in the Western Carpathians at that time. Surrounding temperate forest possibly retained a certain degree of openness, or local steppe habitat may have persisted on adjacent loess terraces until the neolithization of the area. Archaeological evidence represented by a ceramic shard dated to 7339 cal. a BP suggests the first appearance of humans at the site, yet pollen analysis records a significant change in vegetation first at 6650 cal. a BP. The local ecosystem records an abrupt change linked with human settlement earlier, at c.  7000 cal. a BP. Deforestation activities of the Neolithics resulted in the formation of an open calcareous fen occupied by numerous light‐demanding mollusc species. The present study provides new important data about the spread of temperate trees at the onset of the Holocene, about further vegetation changes caused by activities of the first Neolithic farmers and about climate changes in the region of southwestern Slovakia.